Influence of passive smoking on learning in elementary school - Juliana Gomes Jorge; Clóvis Botelho; Ageo Mário Cândido Silva; Gisele Pedroso Moi (Elsevier, 2016)
Objective: To analyze the association between household smoking and the development of learning in elementary schoolchildren. Methods: Cross-sectional study with 785 students from the 2nd to the 5th year of elementary school. Students were evaluated by the School Literacy Screening Protocol to identify the presence of learning disabilities. Mothers/guardians were interviewed at home through a validated questionnaire. Descriptive and bivariate analysis, as well as multivariate Poisson regression, were performed. Results: In the final model, the variables associated with learning difficulties were current smoking at the household in the presence of the child (PR = 6.10, 95% CI: 4.56 to 8.16), maternal passive smoking during pregnancy (PR = 1.46, 95% CI: 1.07 to 2.01), students attending the 2nd and 3rd years of Elementary School (PR = 1.44, 95% CI: 1.10 to 1.90), and being children of mothers with only elementary level education (PR = 1.36, 95% CI: 1.04 to 1.79). Conclusion: The study demonstrated an association between passive exposure to tobacco smoke and learning difficulties at school. Resumo: Objetivo: Analisar a associação entre o tabagismo domiciliar e o desenvolvimento da aprendizagem em escolares do ensino fundamental. Métodos: Estudo transversal, com 785 escolares do 2° ao 5° ano do ensino fundamental. Os alunos foram avaliados por meio do Protocolo de Triagem de Letramento Escolar, visando identificar a presença de dificuldades de aprendizagem. As mães/responsáveis foram entrevistadas no domicílio por meio de questionário validado. Foram realizadas análises descritiva, bivariada e regressão múltipla de Poisson. Resultado: No modelo final, as variáveis associadas às dificuldades de aprendizagem foram tabagismo atual domiciliar na presença do filho (RP = 6,10; IC 95% 4,56-8,16), tabagismo passivo materno durante a gestação (RP = 1,46; IC 95% 1,07-2,01), alunos pertencerem ao 2° e 3° ano do ensino fundamental (RP = 1,44; IC 95% 1,10-1,90) e serem filhos de mães com apenas o nível fundamental de escolaridade (RP = 1,36; IC 95% 1,04-1,79). Conclusão: o estudo evidenciou associação entre a exposição passiva ao tabaco e as dificuldades de aprendizagem nos escolares. Keywords: Smoking, Tobacco smoke pollution, Learning disorders, Children, Palavras-chave: Tabagismo, Poluição por fumaça de tabaco, Transtornos de Aprendizagem, Crianças